Penguatan Tata Kelola Data Ekonomi BUMDes Berbasis Dashboard Informasi Desa di Desa Tabongo Timur - Muhammad Rifai Katili; Lanto Ningrayati Amali; Sri Nilawaty Lahay; Mohamad Syafri Tuloli (Universitas Negeri Gorontalo, 2026)
This community service activity was carried out to strengthen the economic data governance of BUMDes Sinar Usaha toward the development of a village information dashboard in Tabongo Timur Village, Tabongo Subdistrict, Gorontalo Regency. This BUMDes already has active business units, including its flagship product, Sacha Inchi oil